Synthesis and characterization of geopolymers containing blends of unprocessed steel slag and metakaolin: The role of slag particle size. Issue 5 (1st April 2018) - Furlani, E.; Maschio, S.; Magnan, M.; Aneggi, E.; Andreatta, F.; Lekka, M.; Lanzutti, A.; Fedrizzi, L.
Abstract: The present research deals with the production and characterization of geopolymers prepared by mixing metakaolin with a steel slag from the production of chromium-manganese steel, a commercial sodium silicate solution and a sodium hydroxide solution. Different specimens were prepared by mixing metakaolin with different proportions of steel slag (20, 40, 60, 80 wt%) characterized by different maximum particle size. Specimens containing just metakaolin and steel slag alone were also prepared for comparison. All specimens have been characterized regarding their compressive strength, specific surface area, water absorption and microstructure. It has been observed that the use of fine steel slag powders leads to increases the performances and that the specimens containing 40 wt% steel slag and 60 wt% metakaolin revealed the best overall behaviour.